EVALUASI TINGKAT KEPUASAN PASIEN RAWAT JALAN TERHADAP PELAYANAN KEFARMASIAN DI INSTALASI FARMASI RUMAH SAKIT UMUM KARYA BAKTI UJUNG BANDAR RANTAUPRAPAT - Auliafendri, Novycha; Tanjung, Khoiria Ramayani (JIFI (Jurnal Ilmiah Farmasi Imelda), 2021)
Good quality service is an important part that must be provided by health service providers, including hospitals. In providing health services, hospitals are required to provide a sense of security and quality that prioritizes the best interests of patients. Patients who are satisfied with the services provided will have a good perception. Conversely, patients who feel dissatisfied will have a bad perception. The purpose of this study was to determine and measure the quality of pharmaceutical services at the Pharmacy Installation of Karya Bakti General Hospital, Ujung Bandar Rantauprapat, so that a study on the level of outpatient satisfaction with pharmaceutical services at IFRSU was carried out. Karya Bakti Ujung Bandar Rantauprapat. The research was conducted by giving respondents, in this case the patient and the patient's family, a questionnaire to fill out. The questionnaire given contains 23 questions regarding the level of respondent satisfaction with pharmaceutical services at the Pharmacy Installation of Karya Bakti Hospital, Ujung Bandar Rantauprapat. The results of the 5 dimensions of the level of satisfaction include: reliability, reliability, reliability, 83.2%, responsiveness, 85.3%, empathy (empathy) 86.6%, tangibles (direct evidence) 67.28%. , the assurance dimension (guarantee) 84.7%. The results of research on the level of patient satisfaction with pharmaceutical services at the Pharmacy Installation of the Karya Bakti Hospital in Ujung Bandar Rantauprapat can be concluded that the average level of satisfaction of patients and their families with pharmaceutical services at the Pharmacy Installation of RSU Karya Bakti Ujung Bandar Rantauprapat is 81.41%. This means that patients and their families are very satisfied with pharmaceutical services at the Pharmacy Installation of Karya Bakti Hospital, Ujung Bandar Rantauprapat.